The Momentary Enterprise thinking outside the VC box. - Webster, John (SOA webservices journal.)
Prior to the year 2000, business was a world in love with office spaces and corporate travel. We traveled to work (the office) every day. We traveled away from the office for customer meetings, for internal meetings, for conferences, for awards ceremonies. We traveled because we could and we believed that it was necessary for the competitive advantage. That all changed rather quickly with the economic downturn of the early 2000s and, of course, 9/11. In short order, we relearned how to do business by staying put.